2017 IEEE Energy Conversion Congress and Exposition (ECCE) 2017
DOI: 10.1109/ecce.2017.8095894
|View full text |Cite
|
Sign up to set email alerts
|

Design recommendations for energy systems: A UK energy community study

Abstract: Abstract-One of the key elements towards a decentralised energy sector is the consumers' choice and participation, as the concept of energy prosumer is gaining more and more ground and energy community projects are spouting across UK. In order for the upcoming energy systems to deliver their potential financial benefits, holistic design needs to be assessed by quantifying the most relevant design aspects (size and operation) and the energy flow through the energy system. Thus, the predominant aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The model which was used in this study for the battery can be found in [13] and the power converter model in [14]. Briefly, the battery model used is an advanced R in model: a voltage source which varies with the battery SOC, in series with a resistance which depends (inverse proportional) on the battery capacity.…”
Section: Model Usedmentioning
confidence: 99%
“…The model which was used in this study for the battery can be found in [13] and the power converter model in [14]. Briefly, the battery model used is an advanced R in model: a voltage source which varies with the battery SOC, in series with a resistance which depends (inverse proportional) on the battery capacity.…”
Section: Model Usedmentioning
confidence: 99%
“…After structuring the examined system, the optimal energy utilisation (suitable energy management) is defined based on the imported pricing, following the 'cheapest' energy source; the cheapest energy source is always the generated energyself-consumption, whereas the most expensive is to purchase electricity from the power grid during the peak tariff periods. An appropriate and detailed energy management for energy communities with communal ESSs can be found in [24]. Based on the limitations imported during the Imported Parameters stage, and the operational limits of each electric component driven by the selected models (i.e.…”
Section: B Inputs Processingmentioning
confidence: 99%